2020
DOI: 10.1177/1534735420923756
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris Exerts Anticancer Effect on Non–Small Cell Lung Cancer by Inhibiting Hedgehog Signaling via Suppression of TCTN3

Abstract: This study aimed to investigate the effect of Cordyceps militaris extract on the proliferation and apoptosis of non–small cell lung cancer (NSCLC) cells and determine the underlying mechanisms. We performed a CCK-8 assay to detect cell proliferation, detection of morphological changes through transmission electron microscopy (TEM), annexin V–FITC/PI double staining to analyze apoptosis, and immunoblotting to measure the protein expression of apoptosis and hedgehog signaling–related proteins, with C militaris t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Another mechanism of the apoptosis of lung carcinoma by C. militaris extracts is related to downregulation of TCTN3 expression, which affected the hedgehog signaling cascade and contributed to the serial activation of caspases. Additionally, the extract negatively modulated GLI1 transcriptional activity by inhibiting SMO/PTCH1 molecules, subsequently regulating the intrinsic apoptotic signaling cascade [92]. All these findings support the possible use of C. militaris extracts as anticancer agents in future studies.…”
Section: Anticancer Activitysupporting
confidence: 61%
“…Another mechanism of the apoptosis of lung carcinoma by C. militaris extracts is related to downregulation of TCTN3 expression, which affected the hedgehog signaling cascade and contributed to the serial activation of caspases. Additionally, the extract negatively modulated GLI1 transcriptional activity by inhibiting SMO/PTCH1 molecules, subsequently regulating the intrinsic apoptotic signaling cascade [92]. All these findings support the possible use of C. militaris extracts as anticancer agents in future studies.…”
Section: Anticancer Activitysupporting
confidence: 61%
“…Reduction in TCTN3 expression correlated with the suppression of different signaling pathways such as: Smoothened (SMO), Patched1 (PTCH1) and gliomaassociated (GLI1) pathways. The aforementioned processes correlate with decreased Bcl-2, BclxL, and increased Bak, cleaved caspase-3 and caspase-9 levels [92].…”
Section: Antitumor Activity 431 In Vitro Researchmentioning
confidence: 98%
“…Another study reported that the Cm extract overcame cisplatin resistance in NSCLC cell lines when proteomic profile analysis revealed H-Ras down-regulation [ 429 ]. Other authors have demonstrated that its extract down-regulated hedgehog signaling in NSCLCs via TCTN3 inhibition and GLI1 nuclear translocation suppression [ 430 ].…”
Section: Mushroomsmentioning
confidence: 99%